2016
DOI: 10.1089/thy.2015.0316
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Clinicopathologic Characteristics and Survival Outcomes of Anaplastic and Poorly Differentiated Thyroid Carcinoma

Abstract: The choice of treatment of ATC and PDTC could be modified according to resectability and lymphatic invasion of the cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
62
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 39 publications
4
62
0
Order By: Relevance
“…Of the four patients that died from the disease, three had distant metastasis. Reports on this specific topic are not very frequent and there is some inconsistency in the inclusion of anaplastic carcinoma in the same analysis of poorly differentiated, making it hard to establish really reliable data (15).…”
Section: Discussionmentioning
confidence: 99%
“…Of the four patients that died from the disease, three had distant metastasis. Reports on this specific topic are not very frequent and there is some inconsistency in the inclusion of anaplastic carcinoma in the same analysis of poorly differentiated, making it hard to establish really reliable data (15).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that pure ATC (100% undifferentiated component) and ATC arising from PTC/FTC (>10% undifferentiated component, usually > 50%) have a similar behavior and unfavorable prognosis. On the other hand, PTC/FTC with ATC foci (<10% of undifferentiated cells in the background of differentiated cancer) showed significantly better outcome, with a 5‐year survival (81%) exceeding those of ATC (14%) and even of PDC (66%) . Interestingly, the number of cases of pure ATC decreased over the time, while cases of ATC with coincident PTC/FTC became much more frequent (up to half of all ATC) …”
Section: Anaplastic (Undifferentiated) Carcinomamentioning
confidence: 99%
“…Up to half of ATC samples may contain a well‐differentiated component, usually antecedent or coexisting PTC and FTC, or occasionally a minor ATC component is found on postoperative pathological examination of patients with differentiated thyroid carcinoma . Recent Korean studies addressed a significance of coincident ATC and PTC/FTC . It was reported that pure ATC (100% undifferentiated component) and ATC arising from PTC/FTC (>10% undifferentiated component, usually > 50%) have a similar behavior and unfavorable prognosis.…”
Section: Anaplastic (Undifferentiated) Carcinomamentioning
confidence: 99%
“…22) In previous study, both RAI and RT were effective for the improvement of survival of DTC with anaplastic foci and showed no significant difference. 23) Therefore, more research is needed to find out which treatment is more appropriate for DTC with anaplastic foci.…”
Section: Discussionmentioning
confidence: 99%